COMMUNITY WASTE MANAGEMENT EDUCATION: STRATEGIES AND IMPACTS - Nurhayati, Euis; Nurhayati, Sri (JURNAL DIMENSI, 2023)
The research aimed to evaluate the impact of community waste management education on waste handling and disposal practices among the residents of RW 08 in Kecamatan Binong, Kota Bandung. It sought to investigate how participation in education programs influenced community awareness and attitudes towards waste management, as well as to assess the long-term effects of these educational initiatives on the environment and the overall well-being of the community The chosen research methodology was a qualitative case study design, employing semi-structured interviews and participant observation. Thematic analysis and triangulation were utilized to examine the data. The findings underscore the transformative potential of community-driven waste management education programs. Participants not only improved waste management practices but also experienced a mindset shift, perceiving waste as an economic opportunity. Community involvement, hands-on learning, behavior change campaigns, collaboration with local authorities, and incentives were key factors contributing to the program's success. These findings not only advance waste management practices but also demonstrate the potential of community-based initiatives to drive positive change in both environmental and economic dimensions.